Approximate two-component incremental dynamic analysis using a bidirectional energy-based pushover procedure. (15th February 2018) - Soleimani, Sahman; Aziminejad, Armin; Moghadam, A.S.
Highlights: A bidirectional energy-based pushover (BEP) analysis is presented. BEP is used to produce approximate two-component IDA curves. It is applicable to both symmetric and asymmetric buildings. The results show a sufficient degree of accuracy in predicting IDA results. Abstract: Incremental dynamic analysis (IDA) is recognized as a valuable method for assessing the performance of structures under earthquake excitation. Since IDA is computationally intensive, a number of previous studies have attempted to approximate IDA curves using pushover analysis. As a requirement for assessments of asymmetric buildings, IDA under two-component ground motions has received minimal attention throughout these studies. To bridge this gap, the current research puts forth an approximate two-component IDA procedure on the basis of a bidirectional energy-based pushover (BEP) analysis. BEP uses the work done by lateral loads and torques through pushover analysis as an index to determine the characteristics of the modal single-degree-of-freedom systems. The suggested formula pertaining to this procedure allows for the simultaneous effect of both components of a ground motion on each mode. To combine the modal responses of this method, a modified complete quadratic combination (CQC) rule is also presented, which is specialized for two-component excitations. The accuracy of the proposed procedure was examined on a two-way asymmetric 3-story building. The findings suggest that BEP is capable of estimating two-component IDA results with a sufficient degree of accuracy.